Lymphoepithelial Cysts of the Pancreas: The Use of Endoscopic Ultrasound-Guided Fine-Needle Aspiration in Diagnosis - Zamil Karim; Blair Walker; Eric C Lam (Canadian Journal of Gastroenterology)
Lymphoepithelial cysts (LECs) are rare non-neoplastic lesions that can appear as a complex cyst or a mass in the pancreas. Cytology from endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) can be helpful in making a diagnosis with the aim of avoiding unnecessary surgical resection. A case involving a 51-year-old woman with lower abdominal pain who was found to have a multiloculated cystic lesion at the junction of the pancreatic body and tail is described. Cytology from EUS-FNA was consistent with a pancreatic LEC. The lesion was managed conservatively and follow-up imaging of the cyst over the following two years was unchanged. The patient remains clinically well. Cytology from EUS-FNA can help distinguish LECs from cystic neoplasms, thus preventing radical surgical resection of this benign pancreatic cyst.